The Wilms' tumor (WT1) gene expression correlates with the International Prognostic Scoring System (IPSS) score in patients with myelofibrosis and it is a marker of response to therapy. (11th May 2016) - Gallo, Daniela; Nicoli, Paolo; Calabrese, Chiara; Gaidano, Valentina; Petiti, Jessica; Rosso, Valentina; Signorino, Elisabetta; Carturan, Sonia; Bot‐Sartor, Giada; Volpe, Gisella; Frassoni, Francesco; Saglio, Giuseppe; et al.
Abstract: The Wilms tumor gene WT1 is a useful marker of clonal hematopoiesis and it has been shown to be a good marker of residual disease and it reflects the response to therapy. Although myelofibrosis is characterized by mutations of JAK2 and calreticulin (CALR), these mutations are not useful to monitor response to therapy. In this study we demonstrated that in patients affected by myelofibrosis WT1 correlates with the International Prognostic Scoring System (IPSS) score at diagnosis. Furthermore WT1 is a good marker of response to JAK2 inhibitors especially for patients without blasts and for patients who develop anemia or thrombocytopenia not for progression but as therapy related toxicity. Finally, WT1 transcript reduction can mirror a benefit of therapy on the disease burden. This study demonstrated that WT1 is a good marker for monitoring the response to therapy in patients affected by myelofibrosis. Abstract : Although myelofibrosis is characterized by mutations of JAk2 and calreticulin (CALR), these mutations are not useful to monitor response to therapy. WT1 correlates with the International Prognostic Scoring System (IPSS) score at diagnosis. WT1 is a good marker for monitoring the response to therapy.